Análise da penetração de íons cloreto em compósitos cimentícios contendo diferentes teores de escória de alto-forno - Thiago Abdala Magalhães (2019)
The penetration of chloride ions is one of the main factors responsible for reducing the useful life of reinforced concrete structures. These ions, which may eventually be introduced into the concrete from the components of the mixture or penetrate it as a result of the action of the surrounding medium, are capable of provoking the disassembling of the reinforcement, facilitating the establishment of the conditions required for the start of a corrosive process, which is considered the most recurrent and severe pathological manifestation to this type of structure. The present work sought to evaluate the resistance to chloride penetration in concretes produced using special Portland cements containing 0%, 30% and 60% of partial replacement of clinker by blast furnace slag, which were dosed in order to meet to the quality requirements established for environmental aggression classes II and III, with water/cement ratio of 0.55 and 0.60, respectively, as prescribed by the Brazilian standard NBR 6118 (ABNT, 2014). The resistance of the concretes to the penetration of chloride ions was evaluated at 28, 56 and 91 days, using samples obtained from cylindrical specimens measuring (100 x 200) mm, cured in a saturated condition and assayed according to the procedure established by the Finnish standard NT BUILD 492 (NORDTEST, 1999). Furthermore, additional tests were carried out to determine the water absorption by capillarity and by immersion, the voids index and the specific masses, as well as mechanical characterization tests and measurements of electrical resistivity. Microstructural analyzes of the concretes produced were performed using scanning electron microscopy technique. The results showed that the partial substitutions of clinker for blast furnace slag resulted in significant improvements in some of the properties analyzed. The concrete with slag addition presented similar or higher consistency indices when compared to the reference concrete, without additions, with the same water/cement ratio. Regarding the mechanical properties, smaller compressive and tensile strengths were observed in the concrete with slag compared to the reference ones, however, it was observed that, with the advancement of time, the differences between these values decreased and, in view of this and the characteristics of the cements used, it was observed that the concretes with addition still presented capacity of resistance gain in the last analyzed age. The incorporation of blast furnace slag also led to the reduction of water absorption by capillarity and immersion in comparison with the reference concretes. In the range of slag analyzed (between 0% and 60%), these reductions increase in the substitution content. Likewise, lower void indices were obtained as more slag was added. In addition, a significant increase in resistance to chloride ion penetration was observed for all the studied concretes, as well as a considerable increase in their electrical resistivity in relation to the reference concrete with the same age and water/cement ratio. In these cases, it was also observed that the reductions resulting from the substitutions for blast furnace slag were more significant than those resulting from the reduction of the water/cement ratio. There was an effective correlation between the values of surface electrical resistivity and the migration coefficients of chloride ions. The microstructural analysis demonstrated the formation of a more compact and refined cement matrix when blast furnace slag was incorporated into the concretes analyzed.